Burn Pit Emissions Exposure and Respiratory and Cardiovascular Conditions Among Airborne Hazards and Open Burn Pit Registry Participants. Issue 7 (July 2016) - Liu, Jason; Lezama, Nicholas; Gasper, Joseph; Kawata, Jennifer; Morley, Sybil; Helmer, Drew; Ciminera, Paul
Abstract : Objective: The aim of this study was to determine how burn pit emissions exposure is associated with the incidence of respiratory and cardiovascular conditions. Methods: We examined the associations between assumed geographic and self-reported burn pit emissions exposure and respiratory and cardiovascular outcomes in participants of the Airborne Hazards and Open Burn Pit Registry. Results: We found significant dose–response associations for higher risk of self-reported emphysema, chronic bronchitis, or chronic obstructive pulmonary disease with increased days of deployment within 2 miles of selected burn pits ( P -trend = 0.01) and self-reported burn pit smoke exposure ( P -trend = 0.0005). Conclusions: We found associations between burn pit emissions exposure and higher incidence of post-deployment self-reported respiratory and cardiovascular conditions, but these findings should be interpreted with caution because the surrogate measurements of burn pit emissions exposure in this analysis may not reflect individual exposure levels.